PENGEMBANGAN PANDUAN PRAKTIKUM BIOLOGI BERBASIS DIGITAL PADA MATERI JARINGAN HEWAN KELAS XI SMA NURUL FALAH PEKANBARU - Al Khudri Sembiring; Sri Wahyuni; Lilis Agustina (Universitas Lancang Kuning, 2023)
This research is research and development using a modification of the three stages of the 4D development model, namely Define, Design, and Develop. The samples in this study were 2 media experts, 2 material experts, 2 linguists, 1 biology teacher and 10 MIA class XI students from Nurul Falah High School Pekanbaru as respondents. The sampling technique is the Non-Probability sampling technique, namely by using a saturated sample. Data collection techniques used quantitative and qualitative data, namely interviews conducted with biology teachers, filling out questionnaires conducted by 2 media experts, 2 material experts, 2 linguists, 1 biology teacher, and class XI MIA students from Nurul High School Falah Pekanbaru, as well as documentation. The results showed that the average percentage of the validity of the two media experts was 95.36% (very valid), the percentage of the two material experts was 94.58% (very valid), the percentage of the two linguists was 95.33% (very valid). ), the practicality percentage of biology teachers was 88.88% (very practical), and the percentage of student response tests was 87.50% (very practical). Thus, a digital-based biology practicum guideline on animal tissue material is appropriate for class XI students to use.